Entre design de moda e arte: um olhar para a coleção Infinitely Kusama - LOPES, Vanesa Rocha (2014)
This research presents an investigation of some Design’s fields and Contemporary Art, as well, through a look at Infinitely Kusama collection – created by Louis Vuitton’s fashion designer Marc Jacobs, in collaboration with the artist Yayoi Kusama - focusing on her career, her poetics and her installation art. Approaches experience design, which emphasizes affective aspects, symbolic functions and subjective components to delineate appropriations of art forms practiced by Design. Our journey is permeated by the concept of aesthetics experience and leads joints concerning the aesthetics in life, the reproduction, the fetishism of objects and brands, and some of the paradoxes that pervade fashion, such as standardization and differentiation.